Slow Search - Teevan, Jaime; Collins-Thompson, Kevyn; White, Ryen W.; Dumais, Susan (Communications of the ACM, 2014)
We live in a world where the pace of everything from communication to transportation is getting faster. In recent years a number of "slow movements" have emerged that advocate for reducing speed in exchange for increasing quality. These include the slow food movement, slow parenting, slow travel, and even slow science. Building on these movements we propose the concept of slow search, where search engines use additional time to provide a higher quality search experience than is possible given conventional time constraints.